Analisis Cluster dengan K-Means untuk Pengelompokan Kabupaten/Kota di Provinsi Jawa Timur Berdasarkan Pembangunan TIK Tahun 2021-2022 - Hidayati, Rahmatina; Indana, Luthfi; Karyudi, Mochammad Daffa Putra; Sasongko, Redoti Zulfikar (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
The National Statistics Agency has grouped the IP-TIK by province into 4 categories (high, medium, low and very low). However, the details of IP-TIK in each province have not been explained in detail by city or district. The province chosen was East Java. In this province, the Human Development Index (HDI) is at a high level, but there is inequality in the distribution. This research aims to explore information on whether there are gaps in ICT development using a data mining approach, namely grouping. This is so that the East Java Provincial government focuses more on ICT development at the lower level. The method used is k-Means with Euclidean distance calculations. The highest group results are in cluster 2, which indicates that the IP-ICT level in East Java province is on average moderate. Group inequality occurred in cluster 4 for the household having a computer. Those included in cluster 4 (low category) include Pacitan Regency, Lumajang Regency, Probolinggo Regency, Bangkalan Regency, Sampang Regency and Pamekasan Regency.